Accompagner la structuration des écrits des étudiants en travail social - Julie Chabert; Franck Léard; Marc Souet
Confronted increasingly with the difficulties of the students to deliver training writings which are the faithful translation of their thought, the IFTS has put in place an experiment to accompany the future social workers in the structuring of their writings. This support is focused on writing as a process involving multiple regulations and on the collective appropriation of writing training. Collective workshops, plural proofreading and interrogative dialogue with the written material thus invite the students to apprehend writing as a deliberate deliberative act. This article aims to report on an observation process that took place over a year of the educational process to expand and develop this support within our institution. We try to highlight the modalities that allow people in formation to enter the writing, to experience its path and to summon the other, the reader, in their writings.